2023
DOI: 10.3389/fmicb.2023.1177349
|View full text |Cite
|
Sign up to set email alerts
|

The cellular response to ocean warming in Emiliania huxleyi

Abstract: Marine phytoplankton contribute substantially to the global flux of carbon from the atmosphere to the deep ocean. Sea surface temperatures will inevitably increase in line with global climate change, altering the performance of marine phytoplankton. Differing sensitivities of photosynthesis and respiration to temperature, will likely shift the strength of the future oceanic carbon sink. To further clarify the molecular mechanisms driving these alterations in phytoplankton function, shotgun proteomic analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 145 publications
0
4
0
Order By: Relevance
“…This will have a profound influence on ocean-dwelling organisms, as temperature significantly affects metabolic function and enzyme activity. It is predicted that the distribution and ecology of the components of phytoplankton, including dinoflagellates, diatoms and coccolithophores, would change with ocean warming (Hare et al, 2007;Hallegraeff, 2010;Cabrerizo et al, 2014;Dedman et al, 2023). Ocean warming has also been indicated to intensify stratification (Gao et al, 2019), with the upper mixed layer (UML) becoming shallower, which would influence the degree of exposure of organisms in the UML to photosynthetically active radiation (PAR) and UVR (Häder and Gao, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This will have a profound influence on ocean-dwelling organisms, as temperature significantly affects metabolic function and enzyme activity. It is predicted that the distribution and ecology of the components of phytoplankton, including dinoflagellates, diatoms and coccolithophores, would change with ocean warming (Hare et al, 2007;Hallegraeff, 2010;Cabrerizo et al, 2014;Dedman et al, 2023). Ocean warming has also been indicated to intensify stratification (Gao et al, 2019), with the upper mixed layer (UML) becoming shallower, which would influence the degree of exposure of organisms in the UML to photosynthetically active radiation (PAR) and UVR (Häder and Gao, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…An exciting development is the application of single-cell RNA-seq, which was used to profile transcriptomes from individual G. huxleyi cells throughout the viral infection cycle (Ku et al, 2020). Proteomic approaches have been used extensively in G. huxleyi to examine, for example, the cellular responses to warming (Dedman et al, 2023) and to identify processes that are affected by nutrient limitation (McKew et al, 2015;Shire & Kustka, 2022). Metabolomic studies have revealed the importance of mannitol as a carbon storage compound in G. huxleyi (Obata et al, 2013) and identified important metabolic differences between life-cycle stages during nutrient starvation (Wordenweber et al, 2018).…”
Section: Resources For G Hux Le Yi Rese Archersmentioning
confidence: 99%
“…Proteomic approaches have been used extensively in G . huxleyi to examine, for example, the cellular responses to warming (Dedman et al., 2023) and to identify processes that are affected by nutrient limitation (McKew et al., 2015; Shire & Kustka, 2022). Metabolomic studies have revealed the importance of mannitol as a carbon storage compound in G .…”
Section: Resources For G Huxleyi Researchersmentioning
confidence: 99%
“…Microalgae play a key role in marine ecosystems, forming the basis of the marine food chain as they are responsible for almost half of the total primary production (Usher et al, 2014;Dedman et al, 2023). They constitute a potential feedstock because of their valuable metabolites such as pigments, vitamins, proteins, carbohydrates, and lipids with valued fatty acids.…”
Section: Introductionmentioning
confidence: 99%